1989
DOI: 10.1128/iai.57.7.2021-2027.1989
|View full text |Cite
|
Sign up to set email alerts
|

Purification and antimicrobial properties of three defensins from rat neutrophils

Abstract: Three cysteine-rich cationic peptides, designated RatNP-1, RatNP-3, and RatNP-4, were purified from an acid extract of rat polymorphonuclear neutrophils, sequenced, and tested for antimicrobial activity. The peptides ranged from 29 to 32 amino acids in length (Mrs 3,252 to 3,825), and each contained all eight invariantly conserved "framework" residues that are characteristic of defensins. Each of the peptides killed Escherichia coli ML-35, Acinetobacter calcoaceticus HON-1, Staphylococcus aureus 502A, and Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(42 citation statements)
references
References 37 publications
1
40
0
Order By: Relevance
“…29-34 amino acid residues long (M, = 3,500-4,000) and have been found in rats (Eisenhauer et al, 1989), rabbits , and guinea pigs (Selsted & Harwig, 1987), as well as humans (Ganz et al, 1985;Selsted et al, 1985b;Wilde et al, 1989). The amino acid sequences of the defensins have been determined and when they are aligned (Table 1) to emphasize the positions of the conserved residues, a family of cationic peptides is revealed whose net charge varies from +2 for defensin HNP-3 to +9 for defensin NP-1.…”
Section: ~~ ~ ~~~~mentioning
confidence: 99%
See 1 more Smart Citation
“…29-34 amino acid residues long (M, = 3,500-4,000) and have been found in rats (Eisenhauer et al, 1989), rabbits , and guinea pigs (Selsted & Harwig, 1987), as well as humans (Ganz et al, 1985;Selsted et al, 1985b;Wilde et al, 1989). The amino acid sequences of the defensins have been determined and when they are aligned (Table 1) to emphasize the positions of the conserved residues, a family of cationic peptides is revealed whose net charge varies from +2 for defensin HNP-3 to +9 for defensin NP-1.…”
Section: ~~ ~ ~~~~mentioning
confidence: 99%
“…bSources: 'human ; 'human (Wilde et al, 1989); 3guinea pig (Selsted & Harwig, 1987); 4rabbit ; 5rat (Eisenhauer et al, 1989). At pH 7.4, assuming the charge on histidine is neutral.…”
Section: ~~ ~ ~~~~mentioning
confidence: 99%
“…Heterophils were collected as previously described from sterile peritoneal exudates induced in 6-week-old broiler chickens and turkey poults (n = 80) (Sabet et al, 1977;Harmon et al, 1992). The granules were separated from the heterophils and peptides were extracted in acetic acid then purified by size exclusion column chromatography and high pressure liquid chromatography as previously described (Eisenhauer et al, 1989;Yamashita and Saito, 1989;Selsted et al, 1993). Four avian peptides, CHP 1 and 2, and THP 1 and 3 (Evans et al, 1994), were used for the antimicrobial assays described in this study.…”
Section: Avian Heterophil Antimicrobialpeptidesmentioning
confidence: 99%
“…Defensins are cationic antimicrobial peptides that are stored in cytoplasmic granules of neutrophils and some macrophages (reviewed in Lehrer et al, 1991). These unique molecules, first demonstrated by Zeya and Spitznagel (1963), have been isolated from rabbit macrophages and neutrophils (Selsted et al, 1984;Selsted et al, 1985a,b), and human Selsted 1985c;Wilde et al, 19891, guinea pig (Selsted and Harwig, 1987), and rat (Eisenhauer et al, 1989) neutrophils. Sequence analysis of defensins from these species has revealed that they range in size from 29-34 amino acids, eight of which are invariant.…”
mentioning
confidence: 99%